Secure and scalable control plane for intra-domain publish-subscribe communication. (April 2017) - Alzahrani, Bander A.
Abstract: Information centric networking (ICN), using architectures such as the Publish-Subscribe Internet Routing Paradigm (PSIRP), is an emerging research area that proposes a transformation of the current host-centric Internet architecture into an architecture where information items are of primary importance. This change allows network functions such as routing and locating to be optimized based on the information items themselves. This new paradigm has recently gained interest, however, it has not yet been adopted or deployed at a large scale. Therefore, this work examines the scalability of this architecture in real network topologies, using the current and the predicted future Internet traffic as an initial model. In particular, this paper measures the scalability of performing a secure intra-domain routing using a network function termed topology management. The number of topology manager instances for a typical European Internet service provider is estimated from current traffic models of voice, video, peer-to-peer, social networking applications (i.e. Facebook, Twitter), and smart grid applications.